УСЛОВИЯ КУЛЬТИВИРОВАНИЯ И ВЫДЕЛЕНИЯ ПРИРОДНОГО АНТИБИОТИКА № 360, АКТИВНОГО ПРОТИВ МЕТИЦИЛЛИНРЕЗИСТЕНТНЫХ СТАФИЛОКОККОВ С МНОЖЕСТВЕННОЙ ЛЕКАРСТВЕННОЙ УСТОЙЧИВОСТЬЮ (Experimental biology, 2015)
Optimal conditions for cultivation and isolation of antibiotic № 360 active against methicillin-resistant Staphylococci with multiple drug-resistance were selected.
Keywords: methicillin-resistant